O tempo como antagonista na obra Somewhere in Time, de Richard Matheson - Evaristo, Ana Cláudia Ferreira de Queiroz (2012)
The novel Somewhere in Time (1975), by the American author Richard Matheson, presents time as the most relevant element in the elaboration of this novel which ranges between Fantasy and Science Fiction. Time appears in the novel through many perspectives not only as part of the narrative structure, as a character, but also connected to a musical element, more specifically to Gustav Mahler's symphonies. The main focus of this analysis is to reflect about Time and character in the narrative once time is the real antagonist in Matheson s story. In his battle against Time, the character Collier has no control over it, neither in the present time(1971) nor in the past time (1896), considering that he travels back to the past in search of a lost love. The time travel in the novel indicates a reflection about time irreversibility through an immersion into an imaginative world, exposing the intriguing feelings that strike the different historical subjects.